Construct Validity of the Activities Scale for Kids Performance in Children with Cerebral Palsy: Brief Report. (2nd October 2020) - Costi, Stefania; Mecugni, Daniela; Beccani, Laura; Alboresi, Silvia; Bressi, Barbara; Paltrinieri, Sara; Ferrari, Adriano; Pelosin, Elisa
ABSTRACT: Aims : This study collects evidence of construct convergent validity of the Activity Scale for Kids performance (ASKp), comparing its results with the 66-item Gross Motor Function Measure (GMFM-66) and with the Gross Motor Function Classification System (GMFCS) and testing the ASKp's ability to discriminate between individuals with different functional capabilities. Methods : This cross-sectional study involved 60 children with spastic cerebral palsy (CP) assessed with the GMFM-66 who self-administered the Italian version of the ASKp. Results : Children were 10.9 (±3) years old with GMFCS Level I–III. Moderate correlations were found between GMFM and ASKp scores (r = 0.577; p < .001), and between GMFCS levels and ASKp score (rs  = −0.541, p < .001). The ASKp discriminated between children with different functional capabilities, determined by the GMFCS (F = 18.2, p < .001). Conclusions : ASKp is valid to assess physical functioning, a crucial domain in rehabilitation of children with spastic CP. Trial registration : ClinicalTrials.gov Identifier: NCT03325842